DNA polymerase I in constitutive stable DNA replication in Escherichia coli. - Kogoma, T (1997)
We examined the effects of mutations in the polA (encoding DNA polymerase I) and polB (DNA polymerase II) genes on inducible and constitutive stable DNA replication (iSDR and cSDR, respectively), the two alternative DNA replication systems of Escherichia coli. The polA25::miniTn10spc mutation severely inactivated cSDR, whereas polA1 mutants exhibited a significant extent of cSDR. cSDR required both the polymerase and 5'-->3' exonuclease activities of DNA polymerase I. A similar requirement for both activities was found in replication of the pBR322 plasmid in vivo. DNA polymerase II was required neither for cSDR nor for iSDR. In addition, we found that the lethal combination of an rnhA (RNase HI) and a polA mutation could be suppressed by the lexA(Def) mutation.